Exploring anatomical and geographical drivers of the microbiota in wild capybaras (Hydrochoerus hydrochaeris): Baseline Data for zoonotic risk assessment - Milena Camargo; Jorge A. Marín-Sánchez; Plutarco Urbano; Nicolas Luna; Valentina Acevedo Ramírez; Julián A. Rodríguez; Davinzon Martínez; Carlos Porras; Luz H. Patiño; Marina Muñoz; Juan David Ramírez (PLoS ONE, 2026)
Capybaras ( Hydrochoerus hydrochaeris ) play important ecological, cultural, and economic roles in Colombia, particularly in the Orinoco region. Their adaptability to human-modified environments increases contact with humans and animals, raising concerns about their role in zoonotic pathogen transmission. However, their microbiota remains largely unexplored, limiting the understanding of potential health risks relevant to conservation and management. Bacterial communities were characterized in saliva, blood, and feces from 28 wild capybaras in Casanare, Colombia, through 16S-rRNA amplicon sequencing on the Oxford Nanopore platform. Taxonomic profiling was performed with Kraken using the SILVA database. Microbial diversity was assessed in R ( phyloseq , vegan ), and differential abundance across sample types and sites was determined with ANCOM-BC2. After quality control, 196,281 reads were classified into 51 bacterial phyla and 1,779 genera. Proteobacteria, Firmicutes, and Bacteroidetes dominated the phylum-level profiles. At the genus level, composition varied by sample type and location. Fecal samples exhibited the highest bacterial richness and diversity, whereas blood samples displayed the lowest. Beta diversity analysis using Bray–Curtis dissimilarity and PCoA revealed distinct clustering by sample type, supported by PERMANOVA. Site-specific microbial signatures were identified: Blautia and Prevotellaceae UCG-003 were enriched in Paz de Ariporo, while Trinidad showed higher genus-level diversity. Saliva samples displayed the strongest contrasts, with Acinetobacter and Thiobacillus enriched in Trinidad, and Tyzzerella , Arthrobacter , and Histophilus more abundant in Paz de Ariporo. Core microbiota analysis revealed the fewest core genera in blood (one genus), a moderate overlap in saliva (nine genera), and the highest number in feces (13 genera). Distinct patterns in bacterial composition and diversity across sample types and locations were demonstrated in wild capybaras. Both anatomical site and geographic origin influenced the microbiota. These findings provide baseline data to support future research on wildlife microbiota and its potential role in ecosystem health, conservation, and zoonotic transmission.